Quasi-linear heat transport induced by ITG turbulence in the presence of impurities. (22nd October 2020) - Li, J.; Wang, Z.X.; Dong, J.Q.; Shen, Y.; Wang, L.F.; Han, M.K.; Du, H.R.
Abstract: The impurity effects on turbulent transport induced by ion temperature gradient (ITG) turbulence are numerically studied in tokamak plasmas, using a gyrokinetic quasi-linear model. The characteristics of the instability and heat fluxes in the presence of impurity ions are investigated for a broad parameter regime, including temperature and density gradients of main and impurity ions, concentration, charge and mass numbers of impurity ions, magnetic shear as well as wave vector spectrum. The heat fluxes are demonstrated to depend not only on the saturation amplitude of the instability but also on the phase shift between T ˜ s and v ˜ E × B . The peaking factor of temperature/density profile, defined as the ratio of major radius to gradient scale length when the total turbulent heat flux equals zero, is fitted with linear/quadratic functions. In addition, the contributions from diagonal and off-diagonal terms to heat fluxes are identified in detail, i.e. the main ion heat diffusion are proved to be dominated by off-diagonal (diagonal) terms for regions of weak (strong) ITG. In general, steep temperature gradients of main ions as well as hollow density profiles of impurity ions significantly enhance instability and heat fluxes. However, it is interesting to find that the effect of impurity ions with positive density gradient may transit from the enhancement to reduction of the quasi-linear heat flux of main ions in regions of steep ITG, corresponding to transport barriers (e.g. pedestal of H-mode and I-mode plasmas). Both strong and weak positive magnetic shear decrease heat transport.